Colonial constructs : European images of Maori, 1840-1914 - Bell, Leonard (Auckland University Press, 1992)
How did the European settler perceive Maori? What images of Maori society and culture did European artists create for their distant audiences? What preconceptions and aesthetic models lay behind early European depictions of Maori? These are some of the questions explored by art historian Leonard Bell in this major study of the relationship between the visual representation of Maori and the ideology of colonialism. He explores the complex and unbalanced cultural interchange between Europeans and Maori in nineteenth-century New Zealand, in addition to showing how the great range and v.